Poster No. 134 Zebrafish as a tool to study cardiovascular effects caused by fibrillin impairment. (21st October 2022) - de Backer, Julie; de Rycke, Karo; Caboor, Lisa; Vermassen, Petra; Sips, Patrick
Abstract: Introduction: Marfan syndrome (MFS) is the most common type of fibrillinopathy with a high predisposition to develop TAAD. A thorough understanding of the underlying mechanisms is still lacking, indicating a particular need for more flexible in vivo models to address this knowledge gap. Objectives: We aimed to generate a relevant zebrafish model to gain insight into the molecular mechanisms relating fibrillin defects to the cardiovascular system. Methods: The CRISPR/Cas9 system was used to systematically target the three different fibrillin genes ( fbn1, fbn2a and fbn2b ) in Tg(kdrl:GFP) reporter zebrafish. Time-lapse fluorescent microscopy was used to evaluate the cardiovascular phenotype. Results: zebrafish lacking fbn1 and/or fbn2a do not show any cardiovascular phenotype during early-stage development. On the other hand, approximately 50% of homozygous fbn2b mutant ( fbn2b -/- ) zebrafish embryo's show a severe phenotype characterized by endocardial detachment, leading to vascular embolism and premature mortality at 7–9 dpf. Interestingly, the remaining fbn2b -/- zebrafish survive until adulthood, but during larval stages already develop a dilation of the bulbus arteriosus. The caudal vein of all fbn2b -/- embryos also develops abnormally as a cavernous structure lacking vessel integrity. This phenotype is resolved in embryos retaining normal blood flow and aggravated upon pharmacological inhibition of blood flow during development. Conclusion: These data indicate that fbn2b -/- zebrafish model recapitulates cardiovascular complications, and can be considered as a relevant model to study the mechanisms underlying MFS pathogenesis. Our preliminary data suggest that there is an interplay between fibrillin deficiency and biomechanical signaling in the regulation of cardiovascular development.